Characterization of deciduous teeth stem cells isolated from crown dental pulp - Debeljak Martačić, Jasmina; Francuski, Jelena; Lužajić, Tijana; Vuković, Nemanja; Mojsilović, Slavko; Drndarević, Neda; Petakov, Marijana; Glibetić, Marija; Marković, Danica; Radovanović, Anita; Todorović, Vera; Kovačević Filipović, Milica (Vojnosanitetski pregled, 2014)
Background/Aim. The last decade has been profoundly marked by persistent attempts to use ex vivo expanded and manipulated mesenchymal stem cells (MSCs), as a tool in different types of regenerative therapy. In the present study we described immunophenotype and the proliferative and differentiation potential of cells isolated from pulp remnants of exfoliated deciduous teeth in the final phase of root resorption. Methods. The initial adherent cell population from five donors was obtained by the outgrowth method. Colony forming unit–fibroblast (CFU-F) assay was performed in passage one. Cell expansion was performed until passage three and all tests were done until passage eight. Cells were labeled for early mesenchymal stem cells markers and analysis have been done using flow cytometry. The proliferative potential was assessed by cell counting in defined time points and population doubling time was calculated. Commercial media were used to induce osteoblastic, chondrogenic and adipogenic differentiation. Cytology and histology methods were used for analysis of differentiated cell morphology and extracellular matrix characteristics. Results. According to immunophenotype analyses all undifferentiated cells were positive for the mesenchymal stem cell markers: CD29 and CD73. Some cells expressed CD146 and CD106. The hematopoietic cell marker, CD34, was not detected. In passage one, incidence of CFU-F was 4.7 ± 0.5/100. Population doubling time did not change significantly during cell subcultivation and was in average 25 h. After induction of differentiation, the multicolony derived cell population had a tri-lineage differentiation potential, since mineralized matrix, cartilage-like tissue and adipocytes were successfully formed after three weeks of incubation. Conclusion. Altogether, these data suggest that remnants of deciduous teeth dental pulp contained cell populations with mesenchymal stem cell-like features, with a high proliferation and tri-lineage differentiation potential and that these cultures are suitable for further in vitro evaluation of cell based therapies.
Keywords: dental pulp; stem cells; tooth; deciduous; child; preschool; cell differentation; adipogenesis; chondrogenesis; osteogenesis